Effect of The RME Approach Assisted by the Change-It! Media on Students' Mathematical Representation Abilities - Wulandari Wulandari; Isrok'atun Isrok'atun; Ani Nur Aeni (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
This study aims to analyze the effect of the RME approach assisted by Change-It! media on the mathematical representation ability of fourth-grade students. The RME approach was chosen because it provides opportunities for students to build their own mathematical understanding through situations close to their lives, while the Change-It! media is used to help students transform concrete data into various forms of representation. This study uses a quantitative and quasi-experimental approach as its research method. The design used is a nonequivalent control group design and the sampling technique used is purposive sampling. The population in this study were all fourth-grade students in Cimalaka District with the selected samples being Mandalaherang I Elementary School as the experimental class and Cimalaka III Elementary School as the control class. The instrument used was a mathematical representation ability test. The results of this study are that the RME approach assisted by Change-It! media has a significant effect on the mathematical representation ability of fourth-grade students.This is proven by the results of statistical data tests,The average final mathematical representation ability of students after being given the Change-It! media-assisted RME approach was 69.74 with an N-Gain value of 0.55, which is included in the medium category of improvement and the effect of the Change-It! media-assisted RME approach on mathematical representation ability is 54.76%. Meanwhile, the average final mathematical representation ability of students after being given the conventional approach was 48.95 with an N-Gain value of 0.27, which is included in the low category of improvement and the effect of the conventional approach on students' mathematical representation ability is 78%. It is concluded that there is a difference in the influence between the Change-It! media-assisted RME approach and the conventional approach on the mathematical representation ability of fourth-grade students on pictogram material.